Natural‐Light‐Initiated 3D Macro Zigzag Architecture of Graphene‐Reinforced Polystyrene for Gravity‐Driven Oil and Water Separation - Baig, Nadeem (Glob Chall, 2018)
Superhydrophobic 3D robust materials are introduced for the separation of hexane and water. For the first time, novel 3D zigzag polystyrene on graphene‐incorporated polyurethane (3D zz‐PS/GR/PU) is prepared using exclusively natural sunlight without any chemical initiator. The zigzag polystyrene growth is accomplished by polymerizing the styrene vapors. The natural sunlight provides a compact 3D zz‐PS/GR/PU material with superoleophilic and hydrophobic channels that allow for the rapid passage of oil, whereas water is entirely prevented from passing. The 3D zz‐PS/GR/PU compact channels are transformed into the compressible material by treating them with toluene without affecting the hydrophobicity of the material. The 3D zz‐PS/GR/PU displays a high‐water contact angle of approximately 150°. The developed materials are characterized by FTIR, SEM, and BET. The graphene incorporation makes surface area of the 3D zz‐PS/GR/PU substantially large compared with PU. It is improved from 15 to 67 m(2) g(−1). The pore size of the adsorption and desorption in the 3D zz‐PS/GR/PU is also reduced from 354 and 352 Å to 34 and 33 Å. The 3D zz‐PS/GR/PU satisfies the requirement of high‐demanding superhydrophobic materials, like a low‐cost fabrication process, reusability, and tunability. This strategy can trigger large‐scale production with a controlled morphology.